Method and system for manufacturing electrospun composite membranes

JP2026170829APending Publication Date: 2026-10-22FORMOSA TAFFETA CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025100941
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-09
Filing Date
2025-06-17
Publication Date
2026-10-22

Smart Images

  • Figure 2026170829000001_ABST
    Figure 2026170829000001_ABST
Patent Text Reader

Abstract

The present invention provides a method and system for manufacturing electrospun composite membranes. [Solution] A method and system for manufacturing an electrospun composite membrane are provided. The method includes fixing a first base fabric to a conveying device. The conveying device propels the first base fabric and passes it through a first electrospinning device to form a first adhesive fiber layer on the surface of the first base fabric. The conveying device propels the first base fabric having the first adhesive fiber layer and passes it through a second electrospinning device to form a first functional fiber layer on the first adhesive fiber layer of the first base fabric. Then, the conveying device propels the first base fabric having the first adhesive fiber layer and the first functional fiber layer and passes it through a heat-sealing machine to heat-seal the first base fabric having the first adhesive fiber layer and the first functional fiber layer, thereby forming an electrospun composite membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to the field of electrospinning technology, and more particularly to a one-step continuous method for manufacturing electrospinned composite membranes. [Background technology]

[0002] Electrospinning is a technique that uses a high-voltage electrostatic field to extract ultrafine fibers from a solution. This method is used to produce polymer nanofibers, which are commonly used in the textile industry. For example, Patent Document 1 describes a needleless electrospinning technique for the rapid, continuous, and large-scale production of polymer nanofibers, providing a single-layer nonwoven fabric of electrospun nanofibers.

[0003] This electrospinning technology can also be used in the manufacture of composite fabrics. For example, Patent Document 2 describes a process in which an electrospinned film is formed on the surface of a meltblown adhesive film by an electrospinning process, and then the meltblown adhesive film having the electrospinned film is directly heat-pressed onto the surface of a base fabric to form a composite fabric. However, composite fabrics manufactured by forming a laminated film by general melt-blown, coating, and point bonding, and then heat-pressing the laminated film onto a base fabric to cover it, tend to have insufficient breathability.

[0004] Furthermore, current technologies for manufacturing composite fabrics using electrospun yarn typically involve multiple steps. For example, the manufacturing process of the electrospun membrane and the process of attaching the electrospun membrane to the base fabric may be carried out in different factories or processing systems, leading to wasted time and raw materials. As a result, overall processing costs cannot be reduced. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Chinese Patent Application Publication No. 104532482 Specification [Patent Document 2] Taiwan Patent Application Publication No. 202428958 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION

[0006] The present disclosure aims to provide a method for producing an electrospun composite membrane through a one-stop process. An adhesive layer and a functional fiber layer are formed on a base fabric by electrospinning using a continuous conveyor belt. The electrospun composite membrane produced in this manner maintains air permeability and reduces processing costs. MEANS FOR SOLVING THE PROBLEMS

[0007] The present disclosure provides a method for producing an electrospun composite membrane, the method comprising: fixing a first base fabric to a conveying device; propelling the first base fabric by the conveying device to pass through a first electrospinning apparatus, so as to form a first adhesive fiber layer on the surface of the first base fabric; propelling the first base fabric having the first adhesive fiber layer by the conveying device to pass through a second electrospinning apparatus, so as to form a first functional fiber layer on the first adhesive fiber layer of the first base fabric; propelling the first base fabric having the first adhesive fiber layer and the first functional fiber layer by the conveying device to pass through a thermocompression bonding machine, and subjecting the first base fabric having the first adhesive fiber layer and the first functional fiber layer to thermocompression bonding to form the electrospun composite membrane; .

[0008] In the present disclosure, before the first base fabric having the first adhesive fiber layer and the first functional fiber layer passes through the thermocompression bonding machine, the method further comprises: propelling the first base fabric having the first adhesive fiber layer and the first functional fiber layer by the conveying device to pass through a high-temperature oven; propelling the first base fabric having the first adhesive fiber layer and the first functional fiber layer by the conveying device to pass through a third electrospinning apparatus, so as to form a second adhesive fiber layer on the first functional fiber layer; and applying a second base fabric to the second adhesive fiber layer, and passing the resulting structure through the thermocompression bonding machine to form the electrospun composite membrane.

[0009] This disclosure further provides a system for manufacturing electrospun composite membranes, the system is A transport device including an input terminal and an output terminal, A first electrospinning apparatus, which includes an adhesive housing component, is positioned between the input and output terminals of the conveying device. A second electrospinning apparatus, which includes a functional solution containing component, is positioned between the output terminal of the first electrospinning apparatus and the conveying apparatus. The system includes a thermocompression press positioned between a second electrospinning apparatus and the output terminal of a conveying apparatus.

[0010] In this disclosure, the system for manufacturing an electrospun composite membrane further includes a high-temperature oven, a third electrospinning apparatus, and a fabric input device. The high-temperature oven is located between the second electrospinning apparatus and the heat press, the third electrospinning apparatus is located between the high-temperature oven and the heat press, and the fabric input device is located between the third electrospinning apparatus and the heat press.

[0011] In this disclosure, the internal temperature of the high-temperature oven is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.

[0012] In this disclosure, the internal temperature of the high-temperature oven is approximately 60°C to approximately 200°C.

[0013] In this disclosure, the internal temperature of the thermocompression press is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.

[0014] In this disclosure, the heat-sealing temperature of the heat-sealing machine is approximately 80°C to approximately 300°C.

[0015] In this disclosure, the first electrospinning apparatus, the second electrospinning apparatus, and the third electrospinning apparatus are needleless electrospinning apparatuses.

[0016] In this disclosure, the average fiber fineness of the first adhesive fiber layer and the second adhesive fiber layer is equal to or greater than the average fiber fineness of the first functional fiber layer, and the standard weight of the first adhesive fiber layer and the second adhesive fiber layer is equal to or less than the standard weight of the first functional fiber layer.

[0017] In this disclosure, the first adhesive fiber layer and the second adhesive fiber layer each have an average fiber fineness of about 200 nm to about 700 nm and a reference weight of about 1 g / M 2 Approximately 20g / M 2 That is the case.

[0018] In this disclosure, the first functional fiber layer has an average fiber fineness of about 80 nm to about 500 nm and a reference weight of about 1 g / M 2 Approximately 20g / M 2 That is the case.

[0019] In this disclosure, the first functional fiber layer comprises one or more additives selected from water repellents, antibacterial agents, deodorants, mite repellents, and colorants.

[0020] This disclosure provides a one-stop method and system for manufacturing electrospun composite membranes, enabling the manufacture of electrospun composite membranes in the same processing system, saving transportation time and costs by eliminating the need for transportation to other locations for different processes or treatments. Furthermore, the manufacturing method for electrospun composite membranes is typically carried out at temperatures above room temperature. When composite membranes are manufactured in a multi-stop system, the base fabric may undergo heating procedures at each stop. However, since the manufacturing of electrospun composite membranes is completed in the one-stop system provided in this disclosure, the base fabric can be maintained at a temperature above room temperature without undergoing multiple heating treatments, thereby reducing energy consumption. Moreover, in this disclosure, since the adhesive fiber layer is formed by electrospinning, both the adhesive fiber layer and the functional fiber layer on the base fabric are permeable. Therefore, the permeability of the entire electrospun composite membrane can be maintained while reducing processing costs. [Brief explanation of the drawing]

[0021] [Figure 1]Figure 1 is a schematic diagram of a system for manufacturing electrospun composite membranes according to some embodiments of the present disclosure. [Figure 2] Figure 2 is an exploded perspective view of an electrospun composite membrane according to several embodiments of the present disclosure. [Figure 3] Figure 3 is a schematic diagram of a system for manufacturing electrospun composite membranes according to some other embodiments of this disclosure. [Figure 4] Figure 4 is an exploded perspective view of an electrospun composite membrane according to several other embodiments of the present disclosure. [Figure 5] Figure 5 is a scanning electron microscope (SEM) image of the first adhesive fiber layer of an electrospun composite membrane according to some embodiments of the present disclosure (magnification 2,500x). [Figure 6] Figure 6 is a scanning electron microscope (SEM) image of the first adhesive fiber layer of an electrospun composite membrane according to some embodiments of the present disclosure (magnification 10,000x). [Figure 7] Figure 7 is a scanning electron microscope (SEM) image of the first functional layer of an electrospun composite membrane according to some embodiments of the present disclosure (magnification 2,500x). [Figure 8] Figure 8 shows scanning electron microscope (SEM) images of electrospun composite membranes according to some embodiments of the present disclosure (magnification 2,500x). [Modes for carrying out the invention]

[0022] This disclosure will be more easily understood through this detailed description and the examples contained herein. Many specific details are provided to fully understand the examples described herein. However, those skilled in the art will understand that the examples described herein can be carried out without these specific details. Furthermore, the description contained herein should not be considered a limitation on the scope of this disclosure.

[0023] Unless otherwise specified herein, “a,” “the,” and similar terms used in this specification (particularly in the scope of the claims set forth later) are understood to include both singular and plural forms. Furthermore, for clarity, while the dimensions of various parts and areas may be exaggerated in the drawings, they are not depicted to actual scale.

[0024] It should be understood that the numerical ranges cited in this specification are intended to include all subranges contained within them. For example, the range "1 to 10" includes all subranges between the specified minimum value of 1 and the specified maximum value of 10 (e.g., 2 to 8, 3 to 6, or 4 to 9, etc.), and includes two values, i.e., the range where the minimum value is 1 or greater and the maximum value is 10 or less. Because the disclosed numerical ranges are continuous, they include all numbers between the minimum and maximum values. Unless otherwise specified, all numerical ranges shown in this specification are approximate values.

[0025] Furthermore, it is assumed here that all figures are modified by the term "approximately," meaning that numerical variations in measurements and operations caused by the precision of the measuring instruments used are to be expected by those skilled in the art.

[0026] As shown in Figure 1, the system for manufacturing electrospun composite membranes according to this disclosure includes the following: A conveying device 10 includes an input end 11 having a first base fabric reel, an output end 12 having a winding roller, and one or more support rolls 13 positioned between the input end 11 and the output end 12, wherein the conveying device 10 is propelled by a motor, the first base fabric reel holds the first base fabric 91 to be processed, the first base fabric 91 is conveyed to the system, and the processed first base fabric 91 is wound onto the winding roller 12. The first electrospinning apparatus 20 is positioned between the input terminal 11 and the output terminal 12 of the conveying device 10 and includes an adhesive containment component 21 and a plurality of nozzles 22 communicating with the adhesive containment component 21, the adhesive containment component 21 containing an adhesive solution, and when the first electrospinning apparatus 20 is operated, the adhesive is sprayed from the nozzles 22 toward the first base fabric 91. The second electrospinning apparatus 30 is positioned between the first electrospinning apparatus 20 and the output terminal 12 of the conveying apparatus 10, and includes a functional solution container 31 and a plurality of nozzles 32 communicating with the functional solution container 31, the functional solution container 31 containing a functional solution, and when the second electrospinning apparatus 30 is operated, the functional solution is sprayed from the nozzles 32 toward the first base fabric 91. The heat-sealing machine 70 is positioned between the second electrospinning apparatus 30 and the output terminal 12 of the conveying apparatus 10, and the heat-sealing machine 70 includes at least one set of heat-sealing rolls 71 assembled in parallel vertically, and when the heat-sealing machine 70 is in operation, the first base fabric 91 can pass through the heat-sealing rolls 71.

[0027] This disclosure provides a method for producing an electrospun composite membrane for use in a system for producing electrospun composite membranes. Accordingly, the following description will be made with reference to Figure 1. However, the method for producing an electrospun composite membrane provided in this disclosure is not limited to use in a system for producing electrospun composite membranes. The method falls within the scope of protection of this disclosure insofar as it conforms to the spirit and scope of the method disclosed herein, and the scope of protection of this disclosure is defined by the appended claims.

[0028] Referring to Figures 1 and 2, the method for producing an electrospun composite membrane provided in this disclosure includes the following steps: The first base fabric 91 is fixed to the conveying device 10 so that the first base fabric 91 moves from the first base fabric reel to the winding roller at the output end 12 at the input end 11 (as indicated by the arrows in Figure 1). The conveying device 10 propels the first base fabric 91, passes it through the first electrospinning device 20, and forms a first adhesive fiber layer 92 on the surface of the first base fabric 91. The conveying device 10 propels the first base fabric 91 having a first adhesive fiber layer 92 (not shown in Figure 1), passes it through the second electrospinning device 30, and forms a first functional fiber layer 93 (not shown in Figure 1) on the first adhesive fiber layer 92 of the first base fabric 91. The conveying device 10 propels the first base fabric 91 having the first adhesive fiber layer 92 and the first functional fiber layer 93, passes it through the heat-sealing machine 70, and heat-seals the first base fabric 91 having the first adhesive fiber layer 92 and the first functional fiber layer 93 to form an electrospun composite membrane 90. As shown in Figure 2, the electrospun composite membrane 90 can have a three-layer structure including the first base fabric 91, the first adhesive fiber layer 92, and the first functional fiber layer 93, with the first base fabric 91 and the first functional fiber layer 93 being bonded together by the first adhesive fiber layer 92.

[0029] The first base fabric 91 is a surface fabric, which may be woven or nonwoven, and the material includes, but is not limited to, polyester, nylon, polypropylene, polyvinylpyrrolidone, or a combination thereof.

[0030] (First electrospinning apparatus) The first electrospinning apparatus 20 may be a high-voltage electrostatic needle spinning apparatus or a needleless electrospinning apparatus. In some embodiments, the first electrospinning apparatus 20 is a needleless electrospinning apparatus, an open system capable of high-speed spinning, and can be used for mass production. Referring to Figure 1, the first base fabric 91 is positioned above the nozzle 22 of the first electrospinning apparatus 20 as it passes through the apparatus. The nozzle 22 of the first electrospinning apparatus 20 sprays adhesive onto the surface of the first base fabric 91. A high-voltage electric field (the high-voltage power supply voltage is controlled between approximately 50kV and approximately 120kV) causes the solvent in the adhesive to volatilize, forming a first adhesive fiber layer 92 on the first base fabric 91, with an average fiber fineness of approximately 200nm to approximately 700nm and a basic weight of approximately 1g / M 2 Approximately 20g / M 2 That is the case.

[0031] In some embodiments, the first adhesive fiber layer 92 may have an average fiber fineness of about 300 nm to about 450 nm. In some embodiments, the first adhesive fiber layer 92 has an average fiber fineness of about 350 nm to about 400 nm, such that the first adhesive fiber layer 92 and the final electrospun composite membrane 90 have excellent air permeability and flexibility. In some embodiments, the first adhesive fiber layer 92 may have a basis weight of about 2 g / M 2 to about 15 g / M 2 In some embodiments, the first adhesive fiber layer 92 may have a basis weight of about 3 g / M 2 to about 10 g / M 2 By adjusting the fiber fineness of the nanofibers of the first adhesive fiber layer 92, the first adhesive fiber layer 92 has an appropriate pore size, high air permeability and high water resistance, and can provide sufficient adhesive force between the first base fabric 91 and the first functional fiber layer 93. In the present disclosure, the average fiber fineness of the nanofibers of the first adhesive fiber layer 92 is about 200 nm to about 700 nm, so that the first adhesive fiber layer 92 can not only provide high water resistance, but also maintain good adhesiveness.

[0032] Since the first base fabric 91 advances the entire system at a constant speed, the number and density of the nozzles 22 of the first electrospinning device 20 can be adjusted according to the obtained basis weight of the first adhesive fiber layer 92.

[0033] The adhesive containment component 21 may be a tank, pipeline, or other component that contains the adhesive and can supply the adhesive to the nozzle 22 of the first electrospinning apparatus 20. The adhesive material can be selected according to the materials of the first base fabric 91 and the first functional fiber layer 93. In some embodiments, the materials of the first functional fiber layer 93 and the first base fabric 91 are nylon, and the adhesive may also be a nylon-based adhesive, so that the electrospun composite film 90 as a whole has material uniformity and is advantageous for a thermocompression process in a specific temperature range. Furthermore, if the materials of the first base fabric 91, the first adhesive fiber layer 92, and the first functional fiber layer 93 are all nylon, the first base fabric 91, the first adhesive fiber layer 92, and the first functional fiber layer 93 can be melted at the interface, so the structural strength (tensile strength) and interlaminar strength (peel strength) of the electrospun composite film 90 of this disclosure can be further improved.

[0034] In some embodiments, the adhesive is a nylon-based adhesive, and the solvent may be an alcohol solvent. The adhesive has the advantages of being volatile, low-toxicity, and low-corrosive, and is environmentally friendly. The concentration of the adhesive is about 10 wt% to about 20 wt%. In some other embodiments, the adhesive may include polyurethane (PU), polymethyl methacrylate (PMMA), polyvinyl acetate (PVAC), etc. Dimethylacetamide (DMAc) can be used as a solvent for polymethyl methacrylate, and water can be used as a solvent for polyvinyl acetate.

[0035] (Second electrospinning machine) The second electrospinning apparatus 30 may be a high-voltage electrostatic needle spinning apparatus or a needleless electrospinning apparatus. In some embodiments, the second electrospinning apparatus 30 may be a needleless electrospinning apparatus. Referring to Figure 1, the first base fabric 91 having the first adhesive fiber layer 92 is positioned above the nozzle 32 of the second electrospinning apparatus 30 as it passes through the second electrospinning apparatus 30. The nozzle 32 of the second electrospinning apparatus 30 sprays a functional solution onto the first adhesive fiber layer 92 on the first base fabric 91. A high-voltage electric field (the high-voltage power supply voltage is controlled between approximately 50 kV and approximately 120 kV) causes the solvent in the functional solution to volatilize, forming a first functional fiber layer 93 on the first adhesive fiber layer 92 of the first base fabric 91, with an average fiber fineness of approximately 80 nm to approximately 500 nm and a basic weight of approximately 1 g / M 2 Approximately 20g / M 2 That is the case.

[0036] In some embodiments, the first functional fiber layer 93 may have an average fiber fineness of about 100 nm to about 300 nm, and in some embodiments, the first functional fiber layer 93 may have an average fiber fineness of about 150 nm to about 250 nm, and the first functional fiber layer 93 and the final electrospun composite membrane 90 have excellent breathability and flexibility. In some embodiments, the first functional fiber layer 93 has a basic weight of about 2 g / M 2 Approximately 15g / M 2 This is possible. In some embodiments, the first functional fiber layer 93 has a basic weight of approximately 3 g / M 2 From approximately 10g / M 2It is possible that the first functional fiber layer 93 has an appropriate pore size, high breathability and high water resistance, by adjusting the fiber fineness of the nanofibers of the first functional fiber layer 93. In this disclosure, the average fiber fineness of the nanofibers of the first functional fiber layer 93 is about 80 nm to about 500 nm, and the first functional fiber layer 93 can provide high water resistance. Furthermore, if the nanofibers are compressed more densely for the purpose of reducing the pore size, water resistance will improve, but the breathability of the first functional fiber layer 93 may decrease. In some embodiments, the average pore size of the first functional fiber layer 93 may be about 0.5 μm to about 5.5 μm. In some embodiments, the average pore size of the first functional fiber layer 93 may be about 0.75 μm to about 4 μm. In some embodiments, the average pore size of the first functional fiber layer 93 may be about 0.8 μm to about 2 μm.

[0037] Since the first base fabric 91 moves throughout the system at a constant speed, the number and density of the nozzles 32 of the second electrospinning apparatus 30 can be adjusted according to the basic weight of the first functional fiber layer 93 obtained.

[0038] In some embodiments, the average fiber fineness of the first functional fiber layer 93 (see electron microscope image shown in Figure 7) may be equal to or less than the average fiber fineness of the first adhesive fiber layer 92 (see electron microscope image shown in Figure 5). In some embodiments, the ratio of the average fiber fineness of the first functional fiber layer 93 to the average fiber fineness of the first adhesive fiber layer 92 may be about 1:1 to about 1:5. Alternatively, the ratio may be about 1:1.5 to about 1:3. In some embodiments, the base weight of the first functional fiber layer 93 may be equal to or greater than the base weight of the first adhesive fiber layer 92. In some embodiments, the ratio of the base weight of the first functional fiber layer 93 to the base weight of the first adhesive fiber layer 92 may be about 1:1 to about 10:1. Alternatively, the ratio of the base weight of the first functional fiber layer 93 to the base weight of the first adhesive fiber layer 92 is approximately 1.5:1 to approximately 7:1. Alternatively, the ratio of the base weight of the first functional fiber layer 93 to the base weight of the first adhesive fiber layer 92 is approximately 3:1 to approximately 5:1.

[0039] The functional solution containment component 31 may be a tank, pipeline, or other component that contains the functional solution and can supply it to the nozzle 32 of the second electrospinning apparatus 30. The functional solution can be selected according to the desired properties of the electrospun composite membrane 90. In some embodiments, the functional solution may be a nylon-based solution and the solvent may be an alcohol solvent. The concentration of the functional solution is approximately 5 wt% to approximately 15 wt%. The functional solution may also be polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyisopropylacrylamide, or other materials commonly used in the manufacture of electrospun composite membranes. Furthermore, the functional solution may contain one or more additives such as water repellents, antimicrobial agents, deodorants, mite repellents, and colorants (e.g., dyes or pigments) to give different properties to the first functional fiber layer 93 obtained from the functional solution.

[0040] In some embodiments, the functional solution further includes colorants such as dyes and pigments, providing the first functional fiber layer 93 with a variety of color options. By adjusting the amount of colorants (dyes and pigments), rich visual effects can be produced at both dark and light levels, improving the aesthetics and application flexibility of the first functional fiber layer 93. For example, as the concentration of the colorant changes from low to high, the degree of color saturation that the first functional fiber layer 93 can exhibit can change from light to dark. The type and concentration of the colorant can be adjusted as needed.

[0041] In some embodiments, the functional solution contains a nylon copolymer and an alcohol as a solvent. The nylon copolymer and alcohol can impart excellent spinnability to the functional solution. By adding additional additives, high fiber strength and high fiber elongation can be given to the nanofibers of the first functional fiber layer 93, and high hydrophobicity can be imparted to the electrospun composite film 90. In some embodiments, the nylon copolymer may be a copolymer of a copolymer amide and an alkoxy-modified nylon 46 / 66 copolymer to promote dissolution in alcohol and improve the spinnability of the electrospun solution.

[0042] (Thermocompression bonding machine) The temperature of the heat press press machine 70 is higher than the melting point of the material of the first adhesive fiber layer 92 and lower than the melting point of the material of the first functional fiber layer 93. In some embodiments, the hot press temperature inside the heat press press machine 70 is about 80°C to about 300°C. In some embodiments, the hot press temperature inside the heat press press machine 70 is about 90°C to about 260°C. In some embodiments, the hot press temperature inside the heat press press machine 70 is about 100°C to about 200°C. During the heat press process, the first adhesive fiber layer 92, positioned between the first functional fiber layer 93 and the first base fabric 91, can partially melt, while the first functional fiber layer 93 remains in a non-melting state, bonding the first functional fiber layer 93 and the first base fabric 91 together. Since the first adhesive fiber layer 92 can melt at the interfaces with the first functional fiber layer 93 and the first base fabric 91, the first adhesive fiber layer 92 can penetrate into the gaps between the nanofibers of the first functional fiber layer 93 at the interface with the first functional fiber layer 93, and the melted first adhesive fiber layer 92 can penetrate into the gaps between the fibers of the first base fabric 91 from the interface with the first base fabric 91, thereby forming a tight and firm bond. As a result, an electrospun composite film 90 is obtained (see electron microscope image shown in Figure 8).

[0043] The thermocompression press 70 includes at least one set of thermocompression rolls 71 assembled in parallel vertically. The thermocompression rolls 71 may be embossed rolls (i.e., embossed roll bonding) or smooth rolls (i.e., smooth roll bonding). In some embodiments, the roll speed of the thermocompression rolls 71 is about 0.1 m / min to about 10 m / min. In some embodiments, the roll speed of the thermocompression rolls 71 is about 0.5 m / min to about 6 m / min. In some embodiments, the roll speed of the thermocompression rolls 71 is about 1 m / min to about 3.5 m / min.

[0044] The electrospun composite membrane manufacturing system in this disclosure may further include various devices depending on the required properties of the electrospun composite membrane.

[0045] As shown in Figures 3 and 4, the electrospun composite membrane manufacturing system in this disclosure may include the conveying device 10, the first electrospinning device 20, the second electrospinning device 30, and the thermocompression press 70, which are described above and will not be described in detail again here. The system further includes: A high-temperature oven 40 is positioned between a second electrospinning apparatus 30 and a heat-sealing machine 70 and has a plurality of transfer rolls 41. Since the first base fabric 91 moves at a constant speed throughout the system, the time it takes for the first base fabric 91 to pass through the high-temperature oven 40 is controlled by the number and position of the transfer rolls 41, ensuring that the first adhesive fiber layer 92 melts and penetrates the first base fabric 91 and the first functional fiber layer 93, thereby ensuring the adhesive effect. A third electrospinning apparatus 50 is positioned between a high-temperature oven 40 and a heat-sealing machine 70 and includes an adhesive container 51 and a plurality of nozzles 52 communicating with the adhesive container 51, wherein when the third electrospinning apparatus 50 is operated, the adhesive container 51 contains an adhesive solution such that the adhesive is sprayed from the nozzles 52 toward the first base fabric 91. The adhesive of the third electrospinning apparatus 50 may be the same as or different from the adhesive of the first electrospinning apparatus 20, and the adhesive of the third electrospinning apparatus 50 may be selected depending on the material of the first functional fiber layer 93 and the second base fabric 95 to be provided later. A fabric input device 60 is positioned between a third electrospinning apparatus 50 and a heat press machine 70 and configured to input a second base fabric 95 into the system, wherein the second base fabric 95 moves together with the first base fabric 91 and various layers thereon and is pressed by the heat press machine 70.

[0046] As shown in Figures 3 and 4, the first adhesive fiber layer 92 and the first functional fiber layer 93 are formed on the surface of the first base fabric 91 and before passing through the heat-sealing machine, the method for manufacturing an electrospun composite film in this disclosure further includes the following steps. A conveying device 10 propels the first base fabric 91, which comprises a first adhesive fiber layer 92 and a first functional fiber layer 93, through a high-temperature oven 40. The high-temperature oven 40 has a plurality of transfer rolls 41, and the time it takes for the first base fabric 91 to pass through the high-temperature oven 40 is controlled by adjusting the number and position of the transfer rolls 41. The internal temperature of the high-temperature oven 40 is higher than the melting point of the material of the first adhesive fiber layer 92 and lower than the melting point of the material of the first functional fiber layer 93. For example, the internal temperature of the high-temperature oven is approximately 60°C to approximately 200°C. In some embodiments, the internal temperature of the high-temperature oven is approximately 80°C to approximately 180°C. And in some embodiments, the internal temperature of the high-temperature oven is approximately 100°C to approximately 150°C. The first base fabric 91, comprising a first adhesive fiber layer 92 and a first functional fiber layer 93, is passed through the third electrospinning apparatus 50 by a conveying device 10 to form a second adhesive fiber layer 94 (not shown in Figure 3) on the first functional fiber layer 93. The elements and configuration of the third electrospinning apparatus 50 (including the composition of the adhesive) are substantially the same as those of the first electrospinning apparatus 20, or can be adjusted as desired. The second base fabric 95 is applied to the second adhesive fiber layer 94 and, after passing through the heat-sealing machine 70, an electrospun composite film 90 is formed. As shown in Figure 4, the electrospun composite film 90 has a five-layer structure including the first base fabric 91, the first adhesive fiber layer 92, the first functional fiber layer 93, the second adhesive fiber layer 94, and the second base fabric 95. The first base fabric 91 and the first functional fiber layer 93 are bonded together by the first adhesive fiber layer 92, and the second base fabric 95 and the first functional fiber layer 93 are bonded together by the second adhesive fiber layer 94.

[0047] In some embodiments, the electrospun composite film manufacturing systems and methods of the present disclosure include the use of more electrospinning equipment to form an electrospun composite film 90 having a structure of more layers. For example, more adhesive fiber layers and / or more functional fiber layers such as water-repellent fibers, antibacterial fibers, deodorizing fibers, mite-repellent fibers, fibers of different colors, UV-blocking fibers, far-infrared fibers, etc. In some embodiments, a first base fabric pretreatment device may be arranged to pretreatment any surface of the first base fabric 91 before the first adhesive fiber layer 92 is formed. However, the above embodiments do not limit the present disclosure in any way.

[0048] (Examples) (Test items and equipment) Basic weight of the fibers: The weight of the fabric per unit area was determined according to the ASTM D3776 standard.

[0049] Average pore size: The average pore size was determined using a capillary flow porometer from PMI.

[0050] Breathability: Breathability was determined according to the ASTM D737 standard.

[0051] Water vapor permeability: Water vapor permeability was determined according to the JIS L 1099 B1 standard.

[0052] Hydrostatic pressure test: The force exerted by the water column per unit area (in millimeters) is determined according to the JIS L1092-5.1-B standard. A larger value indicates higher hydrostatic pressure resistance (water resistance).

[0053] Peel strength: The coating adhesion of rubber and plastic coated fabrics was measured according to ISO 2411 standard.

[0054] Wash fastness test: AATCC 135-2018 standard: Standard test method for dimensional changes of fabric after home washing. Washing parameters: Normal mode / 20 washes (with laundry powder / in a laundry bag). According to the AATCC 135-2018 washing modes, the value for normal mode is tested at 660±15 RPM.

[0055] Water spray test: Followed AATCC35 standard. The principle is to spray water onto the surface of the sample for 5 minutes and place a weighed absorbent paper on the back of the sample. Then, the weight of the sprayed absorbent paper is measured to determine the water permeability. In this test, the cloth was tilted at a 45° angle to simulate raindrops. The test was continued for 5 minutes. The operating parameters were controlled to 1 g × 2 ft × 5 min (1 g, 5 min @ 2 ft).

[0056] Water vapor resistance: Measurements were taken according to the CNS 15102 L3256 standard for fibers - physiological effects - measurement of thermal and water vapor resistance under steady state.

[0057] (Example 1) In Example 1, a nylon-elastane plain weave fabric was fixed to a conveyor and propelled by the conveyor to pass through a first electrospinning apparatus having a voltage controlled to approximately 80 kV. The first electrospinning apparatus sprayed an ethanol solution (concentration approximately 15 wt%) containing bio-based nylon, used as an adhesive, onto the nylon-elastane plain weave fabric to form a first adhesive fiber layer on the surface of the fabric. The average fiber fineness of this layer was approximately 377 nm, and the basic weight was approximately 2.5 g / M. 2 The nylon-elastane plain weave fabric having the first adhesive fiber layer was then propelled by a conveyor to pass through a second electrospinning apparatus with a voltage controlled to approximately 80 kV. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 276 nm, and the basic weight was approximately 10 g / M 2The average pore size was approximately 0.8 μm. The nylon-elastane plain weave fabric having the first adhesive fiber layer and the first functional fiber layer was further passed through a high-temperature oven heated to approximately 135°C by a conveying device, and then propelled through a third electrospinning device with a voltage controlled to approximately 80 kV. The third electrospinning device sprayed an ethanol solution (concentration approximately 15 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon-elastane plain weave fabric. The average fiber fineness of this layer was approximately 377 nm, and the basic weight was approximately 2.5 g / M 2 Next, the nylon circular knit fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 1 m / min and a hot press temperature of approximately 100°C to obtain the electrospun composite film of Example 1.

[0058] The electrospun composite membrane of Example 1 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 1 had a hydrostatic pressure resistance of approximately 10,000 mmH2O and approximately 0.7 CFM (cubic feet per minute) 3 Breathability ( / min), approximately 20,000g / M 2 *This indicates that it has 24-hour water vapor permeability and a peel strength of approximately 204 g / cm, and has passed a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.1 g) and a wash fastness test (no peeling was observed after 50 washes).

[0059] (Example 2) In Example 2, a nylon fabric was fixed to a conveyor and propelled by the conveyor to pass through a first electrospinning apparatus having a voltage controlled to approximately 50 kV. The first electrospinning apparatus sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon, used as an adhesive, onto the nylon fabric to form a first adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 200 nm, and the basic weight was approximately 2 g / M 2The nylon fabric having the first adhesive fiber layer was then propelled by a conveyor to pass through a second electrospinning apparatus with a voltage controlled to approximately 80 kV. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 5 wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 200 nm, and the basic weight was approximately 3 g / M 2 The average pore size was approximately 1.7 μm. The nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further passed through a high-temperature oven heated to approximately 60°C by a conveying device, and then propelled through a third electrospinning device with a voltage controlled to approximately 50 kV. The third electrospinning device sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 200 nm, and the basic weight was approximately 1.8 g / M 2 Next, another nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 6 m / min and a hot press temperature of approximately 80°C to obtain the electrospun composite film of Example 2.

[0060] The electrospun composite membrane of Example 2 underwent performance tests including hydrostatic pressure resistance, air permeability, water vapor permeability, peel strength, water spray resistance test, and wash fastness test. The results showed that the electrospun composite membrane of Example 2 withstood a hydrostatic pressure of approximately 2,000 mmH2O, had an air permeability of approximately 20 CFM, and a water resistance of approximately 100,000 g / M 2 *This indicates that it has 24-hour water vapor permeability, a peel strength of approximately 207 g / cm, and has passed a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.1 g) and a wash fastness test (no peeling was observed after 50 washes).

[0061] (Example 3) In Example 3, a nylon fabric was fixed to a conveying device and propelled through a first electrospinning apparatus having a voltage controlled to approximately 75 kV. The first electrospinning apparatus sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon, used as an adhesive, onto the nylon fabric to form a first adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 250 nm, and the basic weight was approximately 2.9 g / M. 2 The nylon fabric having the first adhesive fiber layer was then propelled by a conveyor to pass through a second electrospinning apparatus with a voltage controlled to approximately 75 kV. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 5 wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 500 nm, and the basic weight was approximately 3 g / M 2 The average pore size was approximately 5.4 μm. The nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further passed through a high-temperature oven heated to approximately 110°C by a conveying device, and then propelled through a third electrospinning device with a voltage controlled to approximately 75 kV. The third electrospinning device sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 248 nm, and the basic weight was approximately 3.03 g / M 2 Next, another nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 3.5 m / min and a hot press temperature of approximately 100°C to obtain the electrospun composite film of Example 3.

[0062] The electrospun composite membrane of Example 3 underwent hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 3 had a hydrostatic pressure resistance of approximately 1,000 mmH2O, an air permeability of approximately 12 CFM, and a resistance of approximately 120,000 g / m². 2*This indicates that it has 24-hour water vapor permeability and a peel strength of approximately 213 g / cm, and has passed a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.1 g) and a wash fastness test (no peeling was observed after 50 washes).

[0063] (Example 4) In Example 4, the nylon fabric was fixed to a conveyor and propelled by the conveyor to pass through a first electrospinning apparatus having a voltage controlled to approximately 75 kV. The first electrospinning apparatus sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon, used as an adhesive, onto the nylon fabric to form a first adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 250 nm, and the basic weight was approximately 5.2 g / M. 2 The nylon fabric having the first adhesive fiber layer was then propelled by a conveyor to pass through a second electrospinning apparatus with a voltage controlled to approximately 75 kV. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 273 nm, and the basic weight was approximately 7 g / M 2 The average pore size was approximately 1.08 μm. The nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further passed through a high-temperature oven heated to approximately 110°C by a conveying device, and then propelled through a third electrospinning device with a voltage controlled to approximately 75 kV. The third electrospinning device sprayed an ethanol solution (concentration approximately 7 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon fabric. The average fiber fineness of this layer was approximately 252 nm, and the basic weight was approximately 5.1 g / M 2 Next, another nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 2 m / min and a hot press temperature of approximately 100°C to obtain the electrospun composite film of Example 4.

[0064] The electrospun composite membrane of Example 4 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 4 had a hydrostatic pressure resistance of approximately 5,000 mmH2O, an air permeability of approximately 3 CFM, and an air resistance of approximately 70,000 g / M 2 *This indicates that it has 24-hour water vapor permeability and a peel strength of approximately 258 g / cm, and has passed a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.1 g) and a wash fastness test (no peeling was observed after 50 washes).

[0065] (Example 5) In Example 5, a marine recycled nylon fabric was fixed to a conveyor and propelled by the conveyor to pass through a first electrospinning apparatus having a voltage controlled to approximately 80 kV. The first electrospinning apparatus sprayed an ethanol solution containing nylon (concentration approximately 15 wt%), used as an adhesive, onto the marine recycled nylon fabric, forming a first adhesive fiber layer on the surface of the marine recycled nylon fabric. The average fiber fineness of this layer was approximately 350 nm, and the basic weight was approximately 5.2 g / M. 2 The marine recycled nylon fabric having the first adhesive fiber layer then passed through a second electrospinning apparatus with a voltage controlled to approximately 80kV by a conveying device. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 7wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 302nm, and the basic weight was approximately 10g / M 2 The average pore size is approximately 1.1 μm. The marine recycled nylon fabric having the first adhesive fiber layer and the first functional fiber layer is further passed through a high-temperature oven heated to approximately 120°C by a conveying device, and then through a third electrospinning device with a voltage controlled to approximately 80 kV. The third electrospinning device sprays an ethanol solution (concentration approximately 15 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the marine recycled nylon fabric. The average fiber fineness of this layer is approximately 339 nm, and the basic weight is approximately 4.95 g / M 2Subsequently, another marine recycled nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 2 m / min and a hot press temperature of approximately 90°C to obtain the electrospun composite film of Example 5.

[0066] The electrospun composite membrane of Example 5 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 5 had a hydrostatic pressure resistance of approximately 6,000 mmH2O, an air permeability of approximately 2 CFM, and an air resistance of approximately 60,000 g / M 2 *This indicates that it has 24-hour water vapor permeability and a peel strength of approximately 261 g / cm, and passes the water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.2 g) and the wash fastness test (no peeling was observed after 50 washes).

[0067] (Example 6) In Example 6, the recycled marine nylon fabric was fixed to a conveying device and passed through a first electrospinning device having a voltage controlled to approximately 80kV by the conveying device. The first electrospinning device sprayed an ethanol solution containing nylon (concentration approximately 15wt%), used as an adhesive, onto the recycled marine nylon fabric, forming a first adhesive fiber layer on the surface of the recycled marine nylon fabric. The average fiber fineness of this layer was approximately 350nm, and the basic weight was approximately 6.3g / M. 2 The marine recycled nylon fabric having the first adhesive fiber layer then passed through a second electrospinning apparatus with a voltage controlled to approximately 80kV by a conveying device. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 7wt%) containing bio-based nylon onto the first adhesive fiber layer, resulting in an average fiber fineness of approximately 284nm and a basic weight of approximately 11g / M 2A first functional fiber layer with an average pore size of approximately 0.82 μm was formed. The marine recycled nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further passed through a high-temperature oven heated to approximately 120°C by a conveying device, and then through a third electrospinning device with a voltage controlled to approximately 80 kV. The third electrospinning device sprayed an ethanol solution (concentration approximately 15 wt%) containing bio-based nylon toward the first functional fiber layer, resulting in a surface of marine recycled nylon fabric with an average fiber fineness of approximately 352 nm and a basic weight of approximately 6 g / M 2 A second adhesive fiber layer was formed. Then, another marine recycled nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 1 m / min and a hot press temperature of approximately 150°C to obtain the electrospun composite film of Example 6.

[0068] The electrospun composite membrane of Example 6 underwent tests for water pressure resistance, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness. The results showed that Example 6 had a hydrostatic pressure resistance of approximately 8,000 mmH2O, air permeability of approximately 1.4 CFM, and water vapor permeability of approximately 50,000 g / M. 2 *The peel strength was approximately 277 g / cm over 24 hours, and it passed the water spray resistance test (weight difference before and after the test on absorbent paper was approximately 0.2 g) and the wash fastness test (no peeling was observed after 50 washes).

[0069] (Example 7) In Example 7, a marine recycled nylon fabric was fixed to a conveying device and passed through a first electrospinning device having a voltage controlled to approximately 80kV by the conveying device. The first electrospinning device sprayed an ethanol solution containing nylon (concentration approximately 20wt%), used as an adhesive, onto the marine recycled nylon fabric, forming a first adhesive fiber layer on the surface of the marine recycled nylon fabric. The average fiber fineness of this layer was approximately 550nm, and the basic weight was approximately 7.7g / M. 2The marine recycled nylon fabric having the first adhesive fiber layer then passed through a second electrospinning apparatus with a voltage controlled to approximately 80kV by a conveying device. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 15wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 261nm, and the basic weight was approximately 10g / M 2 The average pore size is approximately 0.78 μm. The marine recycled nylon fabric having the first adhesive fiber layer and the first functional fiber layer is further passed through a high-temperature oven heated to approximately 130°C by a conveying device, and then through a third electrospinning device with a voltage controlled to approximately 80 kV. The third electrospinning device sprays an ethanol solution (concentration approximately 20 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the marine recycled nylon fabric. The average fiber fineness of this layer is approximately 526 nm, and the basic weight is approximately 8.2 g / M 2 Subsequently, another marine recycled nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 0.5 m / min and a hot press temperature of approximately 150°C to obtain the electrospun composite film of Example 7.

[0070] The electrospun composite membrane of Example 7 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 7 had a hydrostatic pressure resistance of approximately 9,000 mmH2O, an air permeability of approximately 0.8 CFM, and an air resistance of approximately 20,000 g / M 2 *This indicates that it has 24-hour water vapor permeability, a peel strength of approximately 276 g / cm, and passes water spray resistance tests (weight difference before and after testing using absorbent paper was approximately 0.2 g) and wash fastness tests (no peeling was observed after 50 washes).

[0071] (Example 8) In Example 8, the recycled marine nylon fabric was fixed to a conveying device and passed through a first electrospinning device having a voltage controlled to approximately 120kV by the conveying device. The first electrospinning device sprayed an ethanol solution containing nylon (concentration approximately 20wt%), used as an adhesive, onto the recycled marine nylon fabric, forming a first adhesive fiber layer on the surface of the recycled marine nylon fabric. The average fiber fineness of this layer was approximately 700nm, and the basic weight was approximately 10g / M 2 The marine recycled nylon fabric having the first adhesive fiber layer then passed through a second electrospinning apparatus with a voltage controlled to approximately 120kV by a conveying device. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 15wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. The average fiber fineness of this layer was approximately 250nm, and the basic weight was approximately 20g / M 2 The average pore size is approximately 0.5 μm. The marine recycled nylon fabric having the first adhesive fiber layer and the first functional fiber layer is further passed through a high-temperature oven heated to approximately 150°C by a conveying device, and then through a third electrospinning device with a voltage controlled to approximately 120 kV. The third electrospinning device sprays an ethanol solution (concentration approximately 20 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon-elastane plain weave. The average fiber fineness of this layer is approximately 538 nm, and the basic weight is approximately 10 g / M 2 Subsequently, another marine recycled nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 0.5 m / min and a hot press temperature of approximately 150°C to obtain the electrospun composite film of Example 8.

[0072] The electrospun composite membrane of Example 8 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 8 had a hydrostatic pressure resistance of approximately 20,000 mmH2O, an air permeability of approximately 0.3 CFM, and an air resistance of approximately 8,000 g / M 2*This indicates that it has 24-hour water vapor permeability, a peel strength of approximately 294 g / cm, and passes water spray resistance tests (weight difference before and after testing using absorbent paper was approximately 0.2 g) and wash fastness tests (no peeling was observed after 50 washes).

[0073] (Example 9) In Example 9, the nylon fabric was fixed to a conveying device and passed through a first electrospinning apparatus having a voltage controlled to approximately 80kV by the conveying device. The first electrospinning apparatus sprayed nylon 6, used as an adhesive, onto the nylon fabric, resulting in an average fiber fineness of approximately 213nm and a basic weight of approximately 2.8g / M on the surface of the nylon fabric. 2 A first adhesive fiber layer was formed. The nylon fabric having the first adhesive fiber layer then passed through a second electrospinning apparatus with a voltage controlled to approximately 90 kV by a conveying device. The second electrospinning apparatus sprayed nylon 6, used as a functional solution, toward the first adhesive fiber layer, forming a first functional fiber layer on the surface of the first adhesive fiber layer. This layer has an average fiber fineness of approximately 216 nm and a basic weight of approximately 4 g / M 2 The average pore size is approximately 0.8 μm. The nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further propelled by a conveying device, heated in a high-temperature oven at approximately 200°C, and then passed through a third electrospinning apparatus with a voltage controlled to approximately 90 kV. The third electrospinning apparatus sprayed nylon 6, used as an adhesive, toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon fabric. This layer has an average fiber fineness of approximately 200 nm and a basic weight of approximately 2.5 g / M 2 Next, another nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 1 m / min and a hot press temperature of approximately 260°C to obtain the electrospun composite film of Example 9.

[0074] The electrospun composite membrane of Example 9 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 9 had a hydrostatic pressure resistance of approximately 2,000 mmH2O, an air permeability of approximately 8.2 CFM, and a resistance of approximately 110,000 g / m².2 *This indicates that it has 24-hour water vapor permeability, a peel strength of approximately 204 g / cm, and has passed both a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.1 g) and a wash fastness test (no peeling was observed after 50 washes).

[0075] (Example 10) In Example 10, a marine recycled nylon fabric was fixed to a conveyor and propelled by the conveyor, passing through a first electrospinning apparatus with a voltage controlled to approximately 80kV. The first electrospinning apparatus sprayed an ethanol solution containing nylon (concentration approximately 15wt%), used as an adhesive, onto the marine recycled nylon fabric, forming a first adhesive fiber layer on the surface of the marine recycled nylon fabric. This layer had an average fiber fineness of approximately 355nm and a basic weight of approximately 15g / M 2 The marine recycled nylon fabric having the first adhesive fiber layer was then propelled by a conveyor and passed through a second electrospinning apparatus with a voltage controlled to approximately 80kV. The second electrospinning apparatus sprayed an ethanol solution (concentration approximately 7wt%) containing bio-based nylon, used as a functional solution, toward the first adhesive fiber layer, forming the first functional fiber layer on the surface of the first adhesive fiber layer. This layer has an average fiber fineness of approximately 278nm and a basic weight of approximately 11g / M 2 The average pore size is approximately 0.81 μm. The marine recycled nylon fabric having the first adhesive fiber layer and the first functional fiber layer was further propelled by a conveying device, heated in a high-temperature oven at approximately 120°C, and then passed through a third electrospinning apparatus with a voltage controlled to approximately 80 kV. The third electrospinning apparatus sprayed an ethanol solution (concentration approximately 15 wt%) containing bio-based nylon used as an adhesive toward the first functional fiber layer, forming a second adhesive fiber layer on the surface of the nylon-elastane plain weave. This layer has an average fiber fineness of approximately 343 nm and a basic weight of approximately 15 g / M 2 Next, another marine recycled nylon fabric was applied to the second adhesive fiber layer and passed through a heat press machine. The multilayer structure was heat-pressed at a heat press roll speed of approximately 1 m / min and a hot press temperature of approximately 110°C to obtain the electrospun composite film of Example 10.

[0076] The electrospun composite membrane of Example 10 underwent performance tests including hydrostatic pressure, air permeability, water vapor permeability, peel strength, water spray resistance, and wash fastness tests. The results showed that the electrospun composite membrane of Example 10 had a hydrostatic pressure resistance of approximately 8,000 mmH2O, an air permeability of approximately 1.0 CFM, and an air density of approximately 49,000 g / m². 2 *This indicates that it has 24-hour water vapor permeability and a peel strength of approximately 312 g / cm, and has passed both a water spray resistance test (weight difference before and after the test using absorbent paper was approximately 0.2 g) and a wash fastness test (no peeling was observed after 50 washes).

[0077] The permeability (>0.3 CFM) of the electrospun composite membrane obtained by the method or system of this disclosure is improved because both the adhesive fiber layer and the functional fiber layer are formed by electrospinning technology. As a result, air passes more easily through the electrospun composite membrane, avoiding an irritating heat sensation and improving wearing comfort. In contrast, currently available composite membranes cannot achieve such high permeability.

[0078] Furthermore, the electrospun composite membrane obtained by the method or system of this disclosure exhibits high water vapor permeability (≥8,000 g / m²). 2 It has a 24-hour (*) wicking power, allowing it to quickly wick away sweat and moisture and keep you dry, making it particularly suitable for high-intensity outdoor activities. Despite both the adhesive fiber layer and the functional fiber layer having an average fiber fineness of several nanometers, the electrospun composite membrane still has a hydrostatic pressure resistance of over 10,000 mmH2O, passes water spray resistance tests, and provides excellent water resistance that effectively prevents heavy rain from penetrating from within, making it suitable for use in extreme weather conditions.

[0079] The technical features and benefits of this disclosure are broadly outlined above, which will allow for a better understanding of this disclosure. Persons with ordinary skill in the art to which this disclosure belongs should understand that other structures and processes can be readily modified or designed using the concepts and specific embodiments disclosed above to achieve the same objectives as those of this disclosure. Persons with ordinary skill in the art to which this disclosure belongs should understand that such equivalent structures and methods still fall within the spirit and scope of this disclosure as defined in the appended claims.

Claims

1. A method for producing an electrospun composite membrane, The first base fabric is fixed to the conveying device, The first base fabric is propelled by a conveying device, passed through a first electrospinning device, and a first adhesive fiber layer is formed on one surface of the first base fabric. The first base fabric having the first adhesive fiber layer is propelled by the conveying device, passed through the second electrospinning device, and a first functional fiber layer is formed on the first adhesive fiber layer of the first base fabric. The first base fabric having the first adhesive fiber layer and the first functional fiber layer is propelled by the conveying device, passed through a heat-sealing machine, and the first base fabric having the first adhesive fiber layer and the first functional fiber layer is heat-sealed to form an electrospun composite film. A method for producing an electrospun composite membrane, including [the specified element].

2. Before the first base fabric having the first adhesive fiber layer and the first functional fiber layer passes through the heat-sealing machine, The first base fabric having the first adhesive fiber layer and the first functional fiber layer is propelled by the conveying device and passed through a high-temperature oven. The first base fabric having the first adhesive fiber layer and the first functional fiber layer is propelled by the conveying device and passed through the third electrospinning device to form the second adhesive fiber layer on the first functional fiber layer, The second base fabric is applied to the second adhesive fiber layer, and the electrospun composite film is formed by passing it through the heat-sealing machine. A method for producing an electrospun composite membrane according to claim 1, further comprising:

3. A method for producing an electrospun composite film according to claim 2, wherein the internal temperature of the high-temperature oven is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.

4. A method for producing an electrospun composite film according to any one of claims 1 to 3, wherein the internal temperature of the heat-compression press is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.

5. A method for producing an electrospun composite membrane according to claim 2 or 3, wherein the first electrospinning apparatus, the second electrospinning apparatus, and the third electrospinning apparatus are needleless electrospinning apparatuses.

6. A method for producing an electrospun composite membrane according to claim 2 or 3, wherein the average fiber fineness of the first adhesive fiber layer and the second adhesive fiber layer is equal to or greater than the average fiber fineness of the first functional fiber layer, and the basic weight of the first adhesive fiber layer and the second adhesive fiber layer is equal to or less than the basic weight of the first functional fiber layer.

7. A method for producing an electrospun composite membrane according to any one of claims 1 to 3, wherein the first functional fiber layer comprises one or more additives selected from a water repellent, an antibacterial agent, a deodorant, a mite repellent, or a coloring agent.

8. The first adhesive fiber layer and the second adhesive fiber layer each have an average fiber fineness of 200 nm to 700 nm and a density of approximately 1 g / M, respectively. 2 From 20g / M 2 The basic weight of the first functional fiber layer is 80 nm to 500 nm with an average fiber fineness of 1 g / M 2 From 20g / M 2 A method for producing an electrospun composite membrane according to claim 2 or claim 3, having a basic weight.

9. A system for manufacturing electrospun composite membranes, A transport device including an input terminal and an output terminal, A first electrospinning apparatus, which includes an adhesive containment component, is positioned between the input terminal and the output terminal of the conveying apparatus. A second electrospinning apparatus, which includes a functional solution containing component, is positioned between the first electrospinning apparatus and the output terminal of the conveying apparatus. A thermocompression press is positioned between the second electrospinning apparatus and the output terminal of the conveying apparatus, A system for manufacturing electrospun composite membranes, equipped with the necessary components.

10. A high-temperature oven is positioned between the second electrospinning apparatus and the heat-compression bonding machine, A third electrospinning apparatus is positioned between the high-temperature oven and the heat-sealing machine, A fabric input device is positioned between the third electrospinning apparatus and the heat press machine, A system for producing an electrospun composite membrane according to claim 9, further comprising:

11. A system for producing an electrospun composite membrane according to claim 10, wherein the internal temperature of the high-temperature oven is 60°C to 200°C.

12. A system for producing an electrospun composite film according to any one of claims 9 to 11, wherein the hot press temperature inside the heat-compression press is 80°C to 300°C.

13. A system for producing an electrospun composite membrane according to any one of claims 9 to 11, wherein the first electrospinning apparatus, the second electrospinning apparatus, and the third electrospinning apparatus are needleless electrospinning apparatuses.

Citation Information

Patent Citations

  • Needle-free electrostatic spinning polymer nanofiber large-scale quick continuous manufacturing system

    CN104532482A

  • Breathable and waterproof cloth and manufacturing method thereof

    TW202428958A